Language situation in Belarus and its reflection in the present-day newspaper text: Языковая ситуация в Беларуси и её отражение в современном газетном тексте - Волынец, Татьяна (Rozprawy Komisji Językowej, 2019)
https://doi.org/10.26485/RKJ/2018/65/15 Article in Belarusian The article addresses peculiarities of Belarusian language insertion usage in texts of present day newspapers of Belarus published in Russian as well as bilingual ones. Facts of conscious insertion of alien (Belarusian language) elements into texts written in Russian are investigated on the basis of the data registered by the author in the middle of the 90-ies of the ХХth century – the time when in the language of the newspapers in Belarus a specific sociocultural aggregation of Russian and Belarusian language elements started to be formed. In the course of the research it has been found that in the present-day newspaper text this process a) has kept its major semantico-stylistic properties (the Belarusian word in the Russian text is still being used as means of evaluation, irony, as an appeal to non-textual information, as a signal of the communicative situation “agreement – disagreement”, as an indication of Belarusian socio- or ethnocultural space); b) has acquired new features: the number of insertions of the phrasal and superphrasal levels has significantly grown (journalists use Belarusian texts as an element of intertextual interaction which participates in the formation of intertextuality of modern Belarusian publicistic writing); trasyanka which is a spontaneously russified variant of the Belarusian language started to be introduced into newspaper texts written in Russian; text positions used for the actualization of the Belarusian word have changed (it began to be actively used in headlines and subheadings, in creolized texts); the transformation of social conditions has brought about the transformation of the newspaper senses topical for the newspaper text, as a result the number of lexemes and word combinations thematically related to the designation of concepts and phenomena of socio-political character has sharply decreased among Belarusian language insertions.